To study the present status of Wetlands and Rivers and its diversity near Bhopal district, Madhya Pradesh - Sangma, Silgrim N; Minare, Anubhuti; Vyas, Vipin (AG Volumes, 2025)
The present study was conducted to assess the current status of wetlands and riverine fish diversity in and around the Bhopal district of Madhya Pradesh, with specific focus on regions including Bhopal, Sehore, and Berasia. Field surveys were carried out from multiple water bodies such as the Upper and Lower Lakes of Bhopal (Bhoj Wetlands), the Parbati River in Sehore, and various ponds and reservoirs in Berasia including Goretia Talab, Sagoni Kalan, and Semri Kalan. Data were collected through field observations, interaction with local fishers and vendors, and secondary data sources including scientific literature and IUCN assessments. A total of 54 fish species belonging to 12 orders and 23 families were recorded, with Cyprinidae being the most dominant family comprising 20 species, followed by Bagridae and Channidae. The study noted a concerning decline in the population of Small Indigenous Fish species (SIF), attributed to the presence of invasive and predatory species like Hypophthalmichthys molitrix and Clarias gariepinus, along with anthropogenic pressures such as pollution, habitat degradation, siltation, and unregulated aquaculture. According to the IUCN Red List, the majority of species observed were categorized as Least Concern, while others such as Tor tor were listed as Endangered, Wallago attu as Vulnerable, and species like Ompok bimaculatus and Chitala chitala as Near Threatened or Data Deficient. This study highlights the rich yet threatened fish biodiversity of the Bhopal region and underscores the urgent need for conservation efforts. Recommended strategies include controlling invasive species, promoting sustainable aquaculture, preventing overharvesting, and restoring natural wetland habitats. These actions are vital for preserving the ecological integrity of central India’s freshwater ecosystems and safeguarding indigenous aquatic biodiversity for future generations.